Radiotherapy in children without anesthesia: A feasibility approach using distraction - Aswin Anapathoor Nagarajan; Venkatraman Radhakrishnan; Selvaluxmy Ganesharajah (Indian Journal of Medical and Paediatric Oncology)
Context: Radiotherapy is an important component of treatment of children with cancer. However, delivery of radiotherapy to children is challenging because of the requirement of sedation or anesthesia for immobilization. The present study attempts to highlight our experience of successful delivery of radiotherapy to children with cancer without the use of sedation or anesthesia. Subjects and Methods: The study included pediatric patients <12 years who were treated with radiotherapy at our center between January 2015 and June 2017. Retrospective analysis of patient case records was performed to obtain the treatment details. Results: During the study, 50 children received radiotherapy, among them, 44 (88%) were treated without sedation or anesthesia. The most common diagnosis was acute lymphoblastic leukemia (25%) followed by Ewing's sarcoma (16%) and rhabdomyosarcoma (14%). About 56% of the children belonged to the age group of 1–5 years and 44% belonged to 6–12 years. The latter age group were cooperative and completed the treatment without anxiety. Although the children belonging to 1–5 years age group had anxiety in the commencement of treatment, they completed it without anesthesia, using distraction techniques. There were no treatment delays or physical trauma sustained due to nonusage of sedation or anesthesia. Conclusions: The study shows that with adequate counseling and use of distraction techniques it is possible to deliver radiotherapy to children without the requirement of anesthesia. This practice will be useful for settings were the availability of staff and equipment for anesthesia is limited.